(untitled) (KYAMC Journal, 2020)
Background: Prostate-specific antigen (PSA) is a protein produced by the cells of the prostate gland. It is generally increased in diseases such as prostatitis, hyperplasia and malignancy, but the correlation between various pathology affecting the prostate gland and their corresponding rise in PSA values is not constant, and exception may occur. Objectives: The aim of this study was to find out the spectrum and distribution of various prostatic lesions affecting men, with respect to their age and to find out the correlation between serum total PSA and histological findings. Materials and Method: From January 2016 to March 2019, a total of 166 patients in the age group of 39-95 years who underwent histopathology. The reports were studied retrospective and prospectively. Of these patients, 63 were being nodular hyperplasia of prostate. 70 were with existing prostatitis and 33 were adenocarcinoma. The PSA levels were estimated in our Biochemistry Department. Results: The cases were distributed in the age group 39 to 95years.The patient of adenocarcinoma was 33 and its mean value of PSA was 1164.19 ng/ml, in case of prostatitis number of patient was 70 and its mean value was 12.74ng/ml, prostatic hyperplasia patient was 63 and mean value was 5.2ng/ml. Conclusion: The result indicate that the chances of malignancy with increasing value of PSA are more but not a rule. It can only give a clue to the histopathologist to examine the sections more thoroughly. KYAMC Journal Vol. 11, No.-1, April 2020, Page 42-45